Histomorphochemical Studies on the Trachea of Dalmatian Dog - Anuradha, Anuradha; Bansal, Neelam; Uppal, Varinder (Indian Journal of Veterinary Anatomy, 2015)
The present study was conducted on the trachea of six adult Dalmatian dogs. Samples were processed by routine paraffin technique. Histomorphological observations revealed that trachea was lined by pseudostratified columnar epithelium which consisted of basal, ciliated and mucous cells. Lamina propria was composed of lymphocytes, plasma cells and glands. Histochemical studies showed that the cartilaginous rims of trachea stained blue with PAS/AB while most glandular cells stained red with PAS.